Geodesic of Two Places on the Surface of the Earth and the Direction from One Place Towards the Other (Dhaka University Journal of Science, 2025)
With the help of some standard results in Geometry, Differential geometry, Spherical Trigonometry and the latitude and longitude of two places on the surface of the earth one can measure the Geodesics of the path joining those places and the direction between two places with respect to the geographical position. The study of geodesics on a sphere aroses in connection with geodesy specially with the solution of triangulation networks. The figure of the earth is well approximated by an oblate ellipsoid, a slightly flattened sphere. A geodesic is the shortest path between two points on a curved surface, analogous to a straight line on a plane surface. Instead of finding networks as a two dimensional problem, these problems are now solved by three dimensional methods. The main objectives of this paper is to find the distances and directions of the sum of different renowned places named Dhaka to Mecca, London to Mecca, NewYork to Mecca and Delhi to Mecca with the help of the knowledge of differential geometry.Dhaka Univ. J. Sci. 73(1): 87-92, 2025 (January)